Light-regulated PAS-containing histidine kinases delay gametophore formation in the moss Physcomitrella patens - Ryo, Masashi (J Exp Bot, 2018)
Two-component systems (TCSs) are signal transduction mechanisms for responding to various environmental stimuli. In angiosperms, TCSs involved in phytohormone signaling have been intensively studied, whereas there are only a few reports on TCSs in basal land plants. The moss Physcomitrella patens possesses several histidine kinases (HKs) that are lacking in seed plant genomes. Here, we studied two of these unique HKs, PAS-histidine kinase 1 (PHK1) and its paralog PHK2, both of which have PAS (Per–Arnt–Sim) domains, which are known to show versatile functions such as sensing light or molecular oxygen. We found homologs of PHK1 and PHK2 only in early diverged clades such as bryophytes and lycophytes, but not in seed plants. The PAS sequences of PHK1 and PHK2 are more similar to a subset of bacterial PAS sequences than to any angiosperm PAS sequences. Gene disruption lines that lack either PHK1 or PHK2 or both formed gametophores earlier than the wild-type, and consistently, more caulonema side branches were induced in response to light in the disruption lines. Therefore, PHK1 and PHK2 delay the timing of gametophore development, probably by suppressing light-induced caulonema branching. This study provides new insights into the evolution of TCSs in plants.